Stakeholders’ Perceptions of Integrated Community Case Management by Community Health Workers: A Post- Intervention Qualitative Study - Buchner, Denise L.; Brenner, Jennifer L.; Kabakyenga, Jerome; Teddy, Kyomuhangi; Maling, Samuel; Barigye, Celestine; Nettel-Aguirre, Alberto; Singhal, Nalini (PLoS One, 2014)
Background: Integrated community case management (iCCM) involves delivery of simple medicines to children with pneumonia, diarrhea and/or malaria by community health workers (CHWs). Between 2010 and 2012, an iCCM intervention trial was implemented by Healthy Child Uganda. This study used qualitative tools to assess whether project stakeholders perceived that iCCM improved access to care for children under five years of age. Methods: The intervention involved training and equipping 196 CHWs in 98 study villages in one sub-county in Uganda in iCCM. During the eight-month intervention, CHWs assessed sick children, provided antimalarials (coartem) for fever, antibiotics (amoxicillin) for cough and fast breathing, oral rehydration salts/zinc for diarrhea, and referred very sick children to health facilities. In order to examine community perceptions and acceptability of iCCM, post-intervention focus groups and key respondent interviews involving caregivers, health workers, CHWs and local leaders were carried out by experienced facilitators using semi-structured interview guides. Data were analyzed using thematic analysis techniques. Results: Respondents reported increased access to health care for children as a result of iCCM. Access was reportedly closer to home, available more hours in a day, and the availability of CHWs was perceived as more reliable. CHW care was reported to be trustworthy and caring. Families reported saving money especially due to reduced transportation costs, and less time away from home. Respondents also perceived better health outcomes. Linkages between health facilities and communities were reportedly improved by the iCCM intervention due to the presence of trained CHWs in the community. Conclusions: iCCM delivered by CHWs may improve access to health care and is acceptable to families. Policymakers should continue to seek opportunities to implement and support iCCM, particularly in remote communities where there are health worker shortages.